(3GdSjfeG GdJSLjdjI aj eUQ (B/s - (3eQYi, VjGAs ((3GdEScfOQjI (B:s (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ ,s, 2004)
(3GdcJGH jMJhj Ydi HMK TGed aj eLGd GdSjfeG GdJSLjdjI GdeUQjI efP HOGjI GfTGFgG MJi YGe (B1977 (3h gh cJGH dG jSJZfj Yfg LejY GdeTJZdjf aj GdSjfeG GdeUQjI h GdegJehf HgG h gh jYJHQ GdeQLY GdGhd aj gPG GdeLGd s
Keywords: (3GdSjfeG GdJSLjdjIs; (3eUQs; (3GdSjfeGs